1999
DOI: 10.1046/j.1469-8137.1999.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term phosphorus uptake rates in mycorrhizal and non‐mycorrhizal roots of intact Pinus sylvestris seedlings

Abstract: Short-term phosphate uptake rates were measured on intact ectomycorrhizal and non-mycorrhizal Pinus sylvestris seedlings using a new, non-destructive method. Uptake was quantified in semihydroponics from the depletion of P i in a nutrient solution percolating through plant containers. Plants were grown for 1 or 2 months after inoculation at a low relative nutrient addition rate of 3 % d −" and under P limitation. Four ectomycorrhizal fungi were studied : Paxillus involutus, Suillus luteus, Suillus bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…Nitrogen nutrition research has always been subjected to conflicted results that may be caused by differences in the nitrogen nutrition of mycorrhizal fungal species and their isolates (Termorshuizen and Ket, 1991). Some authors found greater below-biomass of plants at low N availability (Colpaert et al, 1999;Raich and Nadelhoffer, 1989) but even if the below-biomass was greater there was no significant differences in the above-ground biomass (Hobbie and Colpaert, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen nutrition research has always been subjected to conflicted results that may be caused by differences in the nitrogen nutrition of mycorrhizal fungal species and their isolates (Termorshuizen and Ket, 1991). Some authors found greater below-biomass of plants at low N availability (Colpaert et al, 1999;Raich and Nadelhoffer, 1989) but even if the below-biomass was greater there was no significant differences in the above-ground biomass (Hobbie and Colpaert, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ten nonmycorrhizal seedlings followed the same procedure in the absence of fungal inoculum and five plants were immediately harvested to determine %C, δ 13 C and C amounts at inoculation. Plants were transferred 3 d later to 70-cm 3 containers filled with 4.6 g acid-washed, sieved perlite (2 -4 mm particles) (Colpaert et al, 1999). Perlite has a low nutrient buffering capacity so plants are growing in a semihydroponic environment where nutrient addition and nutrient uptake in the plants are equivalent.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Subsequently, containers were centrifuged at 135 g for 30 s in order to remove most of the solution retained in the perlite. Roots and perlite were pulled out of the containers and roots separated from the perlite (Colpaert et al, 1999). Fine roots were detached from coarse roots, mycorrhizas being included in the former fraction.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungi play a key role in the establishment and development of most plants (Colpaert, Tichele, Assche and Laere, 1999;Allen, Swenson, Querejeta, Egerton-Warburton and Treseder, 2003). Among the multiple benefits attributed to mycorrhization, its effect on plant development stands out, since there is widespread proof that mycorrhizas improve plant growth by increasing the absorption surface of the root system (Smith and Read, 1997), selectively absorbing and storing certain nutrients (Colpaert et. al., 1999), solubilizing certain chemicals and making some chemical elements that are normally insoluble, in particular phosphorus, available for the plant (Casarin, Plassard, Hinsinger and Arvieu, 2004;Liu, Loganathan, Hedley and Skinner, 2004).…”
Section: Introductionmentioning
confidence: 99%